Le développement durable dans les formations d’ingénieur en France : comment se situer entre formation professionnelle et « éducation à… » - Philippe Prévost; Alain Jouffray (Éducation et Socialisation)
In French higher education, a national law (law ‘Grenelle 1’ of 2009) requires institutions to have a ‘green plan’, setting the sustainable development strategy for the various assignments. This article, which presents the results of an empirical study of training in agricultural engineering, aims to identify opportunities and difficulties that allow the definition of this strategy about the training mission. This study, which analyzed data collected from institution, teachers and students at the end of training, has a triple interest. First, the diagnostic methodology is original, with teachers, through observation of teaching team meetings, and with students by administering a questionnaire to assess the knowledge on sustainable development at the end of training. Moreover, the results show that a training strategy for sustainable development requires to build collectively the processus within each higher education institution. Finally, the integration of sustainable development in higher education questions the educational content beyond the disciplinary concepts and tools, and can better explain the values to be shared within the institution.